2010
DOI: 10.3354/cr00834
|View full text |Cite
|
Sign up to set email alerts
|

Climate–growth relationships of Qilian juniper Sabina przewalskii in the Anyemaqen Mountains, Tibet

Abstract: Climate-growth relationships were investigated for 5 mountain slopes of the Anyemaqen Mountains on the northeastern Tibetan Plateau, using a tree-ring width network indicating the chronologies of 20 Qilian junipers Sabina przewalskii. Tree growth is mainly controlled by regional climate conditions, which are modulated by altitudinal factors. The tree growth patterns in this region were classified asccording to a west -east orientation. Temperature and precipitation from August to October of the previous year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Most regions of the Tibetan Plateau present recovery trends in the spring and autumn but degradation trends in the summer and winter. The above results were verified in another study, which found that, in the Lhasa area, the NDVI achieves its peak point in July or August and its low point in March and April (Peng et al 2010). Although in the Three Rivers Headwaters Regions of the Tibetan Plateau, the grassland yield has increased a little from 1988 to 2005; it is not to rule out the possibility that grazing pressures have a negative impact on the restoration of grassland ecosystems .…”
Section: Discussion Spatiotemporal Changes Of Ndvisupporting
confidence: 52%
See 1 more Smart Citation
“…Most regions of the Tibetan Plateau present recovery trends in the spring and autumn but degradation trends in the summer and winter. The above results were verified in another study, which found that, in the Lhasa area, the NDVI achieves its peak point in July or August and its low point in March and April (Peng et al 2010). Although in the Three Rivers Headwaters Regions of the Tibetan Plateau, the grassland yield has increased a little from 1988 to 2005; it is not to rule out the possibility that grazing pressures have a negative impact on the restoration of grassland ecosystems .…”
Section: Discussion Spatiotemporal Changes Of Ndvisupporting
confidence: 52%
“…In contract, in grassland and cropland, water balance accounts for 46 % of the NDVI variation (Chu et al 2007). Moreover, climate response analyses have shown that NDVI values are more sensitive to precipitation variations than to temperature variations in the Lhasa area (Peng et al 2010), and that precipitation was the most important factor influencing tree growth in the northeastern Tibetan Plateau (Gao et al 2010). For example, the recovery and protection of alpine grasslands benefited from precipitation variation in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…AMP, AMXP, and AMPS played a more important role in the Changtang alpine steppe region, South Qinghai alpine meadow steppe region, as well as the East Qinghai and Qilian mountain steppe regions. Peng et al [31] similarly analyzed the climate-growth relationships of the Qilian juniper at the Anyemaqen mountain on the northeastern Tibetan Plateau. They indicate that compared with temperature, precipitation has a more important role in tree growth.…”
Section: The Mndvi Response To Climatic Factors At the Observatory Stmentioning
confidence: 99%
“…Rather than a single climatic factor, the NDVI is jointly affected by various factors, such as precipitation, temperature, and evaporation (Peng et al, 2010;Sun et al, 2013;Wang et al, 2015). Table 2 shows that there were significant correlations (P < 0.05) between NDVI and climatic factors (mainly include the monthly average maximum temperature in March to July and September, the monthly average minimum temperature in June and September, the monthly average temperature in March, May to July and September, monthly precipitation in May) in the SRYR.…”
Section: Relationship Between Tree-ring Width Climate and Ndvimentioning
confidence: 99%